2016
DOI: 10.2134/jeq2015.02.0116
|View full text |Cite
|
Sign up to set email alerts
|

Lagdo Dam Flood Disaster of 2012: An Assessment of the Concentrations, Sources, and Risks of PAHs in Floodplain Soils of the Lower Reaches of River Niger, Nigeria

Abstract: The concentrations of the USEPA 16 priority polycyclic aromatic hydrocarbons (PAHs) in soils of the floodplain of the lower reaches of River Niger, Nigeria, were investigated following the Lagdo Dam flood disaster of 2012. The aim was to provide information on the extent of contamination, sources, and risks of PAHs in these soils. The concentrations of Σ16 PAHs in the floodplain soils ranged from 812 to 10,700 μg kg. The benzo(a)pyrene (BaP) toxic equivalence and incremental lifetime cancer risk (ILCR) factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 59 publications
4
16
2
Order By: Relevance
“…Similarly, the total cancer risk for infant and adult in the study sites are greater than the acceptable value of 1 × 10 -6 , indicating that the study sites have potential for human carcinogenic risk indicated as acceptable target excess riskbased action values (1 × 10 -6 ) for exposure stipulated by US-EPA [59]. The obtained results shows that total cancer risk values were in agreement with those reported in contaminated soils from Hong Kong [60] metropolitan soils from China [61 flood plain and urban soils from Nigeria, [24,30,45].…”
Section: Pahs Human Health Risk Assessment Procedures Incremental Lifesupporting
confidence: 67%
See 2 more Smart Citations
“…Similarly, the total cancer risk for infant and adult in the study sites are greater than the acceptable value of 1 × 10 -6 , indicating that the study sites have potential for human carcinogenic risk indicated as acceptable target excess riskbased action values (1 × 10 -6 ) for exposure stipulated by US-EPA [59]. The obtained results shows that total cancer risk values were in agreement with those reported in contaminated soils from Hong Kong [60] metropolitan soils from China [61 flood plain and urban soils from Nigeria, [24,30,45].…”
Section: Pahs Human Health Risk Assessment Procedures Incremental Lifesupporting
confidence: 67%
“…[44][45][46]. The toxicological variables for the estimation of human health risk arising from exposure from observed PAHs are in accordance with the recommended limits [24,30,47]. The ILCR value ≤10 −6 is suggestive of very low risk; 10 −6 to 10 −4 show low risk; >10 −4 to 10 −3 indicative of moderate risk; >10 −3 to 10 −1 indicative of high risk and ≥10 −1 show very high risk.…”
Section: Source Identificationmentioning
confidence: 82%
See 1 more Smart Citation
“…2D, 2E, and 2F; plant mortality did not affect all vegetation homogeneously along the river. These results suggest the presence of toxic elements in the sediments, such as those reported subsequent to other dam disruptions and/or mine tailings spills (e.g., during the Lagdo dam disaster in Cameroon; Tesi et al, 2016; in the Namoi River in Australia, Leonard et al, 2001; and during the Aznalcollar mine tailings spill in Spain, Gallart et al, 1999).…”
Section: Resultsmentioning
confidence: 57%
“…PAHs Determination Using Gas Chromatographic Gas chromatograph (HP 6890 Palo Alto, C A, USA) with a flame ionization detector (FID) was used to quantify each PAH in the extracts as described by Tesi et al, and Iwegbue et al [2,3]. Separation was carried out using HP5 (cross-linked PHME siloxane) column with dimensions of 0.25 µm × 30 m and 0.25 µm film thickness.…”
Section: Pahs Extraction and Clean-upmentioning
confidence: 99%